Badan Layanan Umum Perguruan Tinggi dalam Konteks Hukum Ekonomi Syariah - Zulaikha, Siti; Setyawan, Dharma; Ferliadi, Agus Salim; Jayai, Tiara Juliana; Maysaroh, Watim; Hasnan, Odi; Sari, Nurul Rusita (ASAS, 2024)
This research aims to analyze the position of IAIN Metro's Public Service Agency (BLU) as a legal subject in the perspective of sharia economic law. Against the backdrop of IAIN Metro's vision oriented towards socio-eco-techno-preneurship synergy, this research explores the implementation of a legal entity in the context of public services that focuses not only on profit, but also on efficiency and productivity. The research method used is a qualitative method that uses interviews, documentation, and observation, to obtain comprehensive and in-depth data. The results showed that IAIN Metro's BLU is in a positive growth phase, both in terms of revenue and assets. In addition, this research identifies the contractual arrangements in the partnership undertaken by the BLU, as well as provides practical recommendations for legal policies that support the management of legal entities in the public sector. The findings are expected to make a significant contribution to the development of Islamic economics in Indonesia, as well as enrich the literature on the role of legal entities in the context of public services.Keywords: Public Service Agency; Sharia Economic Law; Partnership